Australia's Fiscal Framework : Revisiting Options for a Fiscal Anchor - Dizioli, Allan (IMF Working Papers; Working Paper ;, 2017)
This paper revisits options for fiscal anchors in Australia against the backdrop of a medium-term budget balance anchor that has led to larger than expected upward drift in the net debt to GDP ratio since the end of the mining investment boom. The IMF's G20MOD model is used to compare the budget balance anchor with a long-term debt anchor. Using model simulations evaluated against objective macro stabilization-debt control criteria under three likely scenarios for the Australian economy, the latter is found to perform at least as well as the former. The paper also considers the operationalization of a long-term debt anchor utilizing a combination of fiscal rules which includes expenditure restrictions and a flexible time horizon for convergence, aiming at encouraging countercyclical fiscal policy and minimizing the cost in terms of real GDP foregone in the medium term under fiscal consolidation.